The Effect of Progressive Muscle Relaxation on Blood Sugar Levels in Patients with Type 2 Diabetes Mellitus - Sani, Fakhrudin Nasrul; Rayasari, Fitrian; Anggraini, Dewi; Agung, Rizki Nugraha; Wahyuningsih, Retno Dyah (Indonesian Journal of Global Health Research, 2025)
One of the most complex chronic diseases is diabetes, which requires ongoing medical care aimed at reducing multifactorial risks beyond glycaemic control. Diabetes and stress are interrelated, where stress results in increased cortisol production, cortisol itself inhibits the work of insulin, this triggers an increase in blood sugar levels. One of the ways to control blood sugar levels by providing non-pharmacological therapy is to provide music therapy, relaxation and guided imagery. Progressive Muscle Relaxation (PMR) is one of the relaxations that can be applied to patients with diabetes mellitus. This relaxation technique can speed up the body's metabolism by physiologically increasing blood flow. This study aims to determine the effect of progressive muscle relaxation on blood sugar levels in patients with type 2 diabetes mellitus. This research is a quasi-experimental. The research design used is nonrandomised pretest - posttest with control group design. The research sample was divided into two groups, the intervention group and the control group. Blood sugar level measurements were carried out in the intervention group twice, namely before (pretest) and after (posttest) being given progressive relaxation therapy, while the control group did not receive any actions. The population in this study were patients with type 2 diabetes mellitus at Dr Moewardi Surakarta Hospital. Data analysis using the parametric paired t-test because the data is normally distributed. The blood sugar level in the control group before the relaxation intervention was an average of 237.90 mg/dl and after the relaxation intervention was an average of 218.57 mg/dl. The average blood sugar level in the control group before relaxation was 238.10 mg/dl and after relaxation was 231.43 mg/dl. The p-value for the intervention group based on the paired sample t-test statistic is 0.000 (p < 0.05) with an average decrease in blood sugar level of 19.33 mg/dl. These results indicate that progressive muscle relaxation exercises have an effect on changes in blood sugar levels in patients with type 2 diabetes mellitus. Based on the above description, it can be concluded that progressive muscle relaxation has an effect on changes in blood sugar levels in patients with type 2 diabetes mellitus.